Breaking the norm: An empirical investigation into the unraveling of good behavior - Hill, Ruth Vargas; Maruyama, Eduardo; Viceisza, Angelino (Elsevier, 2012)
We present results from an artefactual field experiment conducted in rural Peru that considers whether observing non-reciprocal behavior influences an individual's decision to reciprocate. Specifically, we consider the behavior of second movers in a trust game, assessing whether their decision to reciprocate is influenced by the observed reciprocity of others. In documenting the impact of an external shock to observed reciprocity, this paper shows that small increases in non-reciprocal behavior result in an unraveling of the norm of reciprocity. Survey data is used to explore mechanisms by which this occurred. Results are not consistent with learning effects, suggesting that preferences may be changed by observing others deviating from a norm of reciprocity. These results suggest that investing in encouraging trustworthy behavior can have large benefits in situations where individuals are observing each other's behavior, such as may be the case in a new market institution.